Flat sheet metal girder with very thin metal web : Part 3 : Sheet metal girders with spars resistant to bending - the stress in uprights - diagonal tension fields - Wagner, Herbert, 1900-1982 (National Advisory Committee for Aeronautics, 1931)
This report continues the work presented in NACA-TM 605 and expands the scope to include the change in specific number of wrinkles from direction x to z, so that b and f become variable in direction z. Moreover, it seems likely that b and f increase from the edge toward the center if the sheet is infinitely thin.
"February, 1931."
NACA TM No. 606.
Translated from Zeitschrift fur Flugtechnik und Motorluftschiffahrt. Vol. 20, No. 11, pp. 281-284, June 14, and No. 12, pp. 306-314, June 28, 1929, by the National Advisory Committee for Aeronautics.
Keywords: Sheet-metal.; Girders.; Mathematics.; Struts (Engineering); Strains and stresses.; Bending.; elektronické knihy; electronic books